Prevalence, Conversion and Reversion of Tuberculosis Infection Among Healthcare Workers of Tertiary Care Centres in Puducherry, India: A Prospective Cohort Study - Sadhana Subramanian; Palanivel Chinnakali; Senbagavalli Prakashbabu; Guha Nandhini Visvanadane; Manju Rajaram; Vijay Viswanathan; Sonali Sarkar; Charles Robert Horsburgh (Tropical Medicine and Infectious Disease)
Healthcare workers (HCWs) face an increased risk of tuberculosis (TB) due to occupational exposure. This study aimed to estimate the point prevalence of TB infection (TBI) from the initial test performed, while the reversion and conversion were done by subsequent testing at one year among HCWs in Puducherry, India. A prospective cohort study was conducted among a sample of proportionately chosen HCWs based on their occupational strata of a tertiary hospital in 2022. TBI was assessed using IGRA (4th generation QuantiFeron—TB gold plus kits) after TB symptom screening. The IGRA test was repeated at the end of one year. Reversion was defined as a positive IGRA test at the baseline and had values < 0.2 IU/L in TB1 or TB2 tubes during follow-up. Conversion was defined as a negative IGRA result at the baseline and had values of >0.7 IU/L in TB1 or TB2 tubes during follow-up. Of the 400 HCWs included, the mean (SD) age was 37 (7) years. Median (IQR) work experience was 15.7 (10–21) years. TBI was seen in 150 HCWs (37.7%, 95% CI: 33.0–42.7), and one had active TB. A total of 128/150 HCWs with TBI at baseline were followed up, and 15 had TBI reversion (11.7 per 100 person-years; 95% CI: 6.7–18.5). Thirteen HCWs (5.6 per 100 person-years; 95% CI: 3.3–9.8) had TBI conversion.